2008
DOI: 10.1158/1078-0432.ccr-08-0862
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide and Rituximab in Waldenstrom's Macroglobulinemia

Abstract: Purpose: Thalidomide and its more potent immunomodulatory derivative lenalidomide enhance rituximab-mediated antibody-dependent cell-mediated cytotoxicity. We therefore evaluated lenalidomide and rituximab in symptomatic Waldenstrom's macroglobulinemia (WM) patients naive to either agent. Experimental Design: Intended therapy consisted of 48 weeks of lenalidomide (25 mg/d for 3 weeks and then 1week off) along with rituximab (375 mg/m 2 /wk) dosed on weeks 2 to 5 and 13 to 16. Sixteen patients were enrolled, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 25 publications
2
65
1
Order By: Relevance
“…Nevertheless, the minimal myelotoxicity of thalidomide may be important for selected patients with severe cytopenias (especially those with severe thrombocytopenia). Lenalidomide with rituximab was associated with significant hematologic toxicity 39 ; thus, it should only be considered in the context of a clinical trial. Pomalidomide is under investigation.…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%
“…Nevertheless, the minimal myelotoxicity of thalidomide may be important for selected patients with severe cytopenias (especially those with severe thrombocytopenia). Lenalidomide with rituximab was associated with significant hematologic toxicity 39 ; thus, it should only be considered in the context of a clinical trial. Pomalidomide is under investigation.…”
Section: Immunomodulatory Drugsmentioning
confidence: 99%
“…by guest www.bloodjournal.org From occurrence of the rituximab-mediated IgM flare can vary considerably and appear dependent on both the regimen used as well as the sequencing of rituximab administration. 40,43,48,[61][62][63] Because of concern over a rituximab-related IgM flare aggravating serum viscosity levels or IgM-related morbidity, the omission of rituximab can also be considered for the first 1 or 2 cycles of treatment. Serum IgM levels should be closely monitored (at least weekly) during the time patients are receiving rituximab-based therapy.…”
Section: Treatment Of the Wm Patient Requiring Immediate Disease Controlmentioning
confidence: 99%
“…The IgM flare may last for several weeks, and even months, and does not per se herald treatment failure. 54,62 The use of rituximab is best avoided as single-agent therapy in patients with high IgM levels because in 2 studies considerably lower response rates were observed in those patients with higher serum IgM levels (Ͼ 4000 mg/dL). 64,65 …”
Section: Treatment Of the Wm Patient Requiring Immediate Disease Controlmentioning
confidence: 99%
See 2 more Smart Citations